AGE, PARENTAL FACTORS, AND INFORMATION SOURCES IN MENSTRUAL HYGIENE KNOWLEDGE OF ADOLESCENT GIRLS - Oktavirona Oktavirona; Kursih Sulastriningsih; Muhamad Aviansyah (Getsempena Health Science Journal, 2026)
Adolescents in general face the same problems in understanding reproductive health, namely a lack of knowledge about sexuality and reproductive health caused by limited access to information and advocacy for adolescents, the absence of access to services that are friendly to adolescents, the absence of an adolescent reproductive health curriculum in schools, and There are still limited government institutions that deal specifically with teenagers and there are no laws that accommodate the rights of teenagers. The results of the 2007 Indonesian Adolescent Reproductive Health Survey (SKRRI), stated that knowledge of adolescents aged 15-24 years about reproductive health was still low, 21% of adolescent girls did not know at all about the changes that occur during puberty. This type of research is descriptive using primary data conducted through a cross sectional design. The sampling technique uses Simple Random Sampling. The analysis used is univariate analysis in the form of percentages and bivariate analysis using the Chi Square Test. From the results of the research, it was found that the frequency distribution of adolescent girls' knowledge was mostly good, 36 female students (78.3), female students with good knowledge based on age of maturity were 42 female students (91.3.5%), good knowledge based on middle school education was 21 female students ( 45.7%), good knowledge based on mothers who do not work as many as 23 female students (50%), good knowledge based on < 2 sources of information, namely 36 female students (78.3%), good knowledge based on behavior as many as 24 female students (52.2%). %). There is a relationship between the knowledge of young women and sources of information, there is no relationship between the knowledge of young women and age at manarche, mother's education, mother's occupation, menstrual personal hygiene behavior. Conclusion: The knowledge of young women about menstrual personal hygiene is mostly good. There is a relationship between the knowledge of young women and sources of information, there is no relationship between the knowledge of young women and age at manarche, mother's education, mother's occupation, menstrual personal hygiene behavior.